Risk Factors, Early Trauma Management and Outcome in children presenting with ocular trauma in a Public Sector Tertiary Care Hospital – a cross sectional study - Usman, Muhammad; Fatima, Anum; Iqbal, Muniba; Baloch, Hiba; Farukh, Khubair; Sheikh, Hassan; Rao, Fatima Shakeel; Iqbal, Zohaib; Ejaz, Hadia; Kulsoom, Afifa (Students’ Supplement of Journal of Rawalpindi Medical College, 2024)
Introduction: Ocular trauma is an important, preventable, worldwide public health problem. Ocular injury is also the cause of acquired blindness and lifelong disability in children. Objective: To assess risk factors, early trauma management and outcome in children presenting with Ocular Trauma in a public sector tertiary care hospital of Rawalpindi. Materials and Methods: A descriptive cross-sectional study was conducted at Holy Family Hospital, Rawalpindi over a period of six months. Data was collected through a Self-structured mixed questionnaire. The demographic data and characteristics of injury events were noted. A detailed medical history was acquired. Visual acuity before and after treatment was recorded. Results: Children aged 6-15 years suffered most ocular injuries. 41 (62%) were males and 25 (38 %) were females. A significant difference in occurrence between rural (32%) and urban (68%) children was revealed. The most frequent place of injuries turned out to be home (46%). Conclusion: Considering the prevalence of ocular trauma, appropriate education and awareness should be given to parents to reduce the risk of trauma. Most eye injuries in children are preventable, reflecting the importance of adult supervision and health literacy for reducing the incidence and severity of trauma.